1970
DOI: 10.1111/j.1528-1157.1970.tb03905.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Serum Primidone Levels

Abstract: SUMMARY The serum half‐life of primidone was determined in 6 subjects and was found to be 10 to 12 hours. In 2 subjects who were taking phenobarbital, no difference in the absorption curve and serum half‐life of primidone was noted. This suggests that phenobarbital does not influence the half‐life of primidone. No detectable phenobarbital was present in the serum of the volunteer subjects following the single 500 mg dose of primidone, even up to 48 hours. This suggests that the bioconversion of primidone to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…Both Booker et al (1970) and Gallagher and Baumel (1972) found the average t max after single oral doses to about 3 hours with a fairly wide range (0.5 to 9 hours). After continued administration the absorption was slower, but this problem as well as the magnitude of the absorbed fraction do not seem to have been investigated closely.…”
Section: Absorptionmentioning
confidence: 96%
“…Both Booker et al (1970) and Gallagher and Baumel (1972) found the average t max after single oral doses to about 3 hours with a fairly wide range (0.5 to 9 hours). After continued administration the absorption was slower, but this problem as well as the magnitude of the absorbed fraction do not seem to have been investigated closely.…”
Section: Absorptionmentioning
confidence: 96%
“…The acute adverse events were related to primidone alone, because they were reported by 13 patients before its metabolites, phenobarbital and phenylethylmalonamide (PEMA), were identified in serum during the initiation of prirnidone therapy (4). By the same token, adverse events occurred in healthy volunteers given primidone at a dosage of 500 mglday, which yielded a serum concentration of 10 mg/l (8).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma level of phenobarbitone appears to be a more useful guide in therapy than that of the parent compound during chronic administration (Booker et al, 1970). Each tablet produces in some extent phenobarbitone and another active anticonvulsant metabolite (PEMA) when chronically administered.…”
Section: Treatment Of Grand Mal and Focal Epilepsiesmentioning
confidence: 99%